An Empirical Study of the Factors Affecting Investment Choice Decisions of Academic Professionals (International Journal of Scientific Research in Science and Technology, 2025)
Investment decisions are influenced by multiple factors that shape an individual's approach to financial planning and wealth management. This study examines the key determinants of investment choice decisions, focusing on financial market awareness, investment objectives, market conditions, risk & return preference, liquidity, and tax considerations. Using a structured questionnaire, primary data was collected from 233 respondents, and the responses were analyzed through Exploratory Factor Analysis (EFA) and ANOVA to identify significant patterns and demographic influences. EFA extracted six distinct factors, each demonstrating strong reliability, highlighting the internal consistency of the constructs. The Total Variance Explained indicated that these six factors collectively accounted for 67.94% of the variance, reinforcing their significance in investment decision-making. ANOVA results revealed that academic position significantly influences financial market awareness, while qualification impacts tax considerations. These findings suggest that investment preferences vary based on professional and educational backgrounds, emphasizing the role of financial knowledge and institutional exposure in shaping investment behavior. These insights emphasize the need for targeted financial education and strategic investment advisory services to address diverse investor needs. Financial institutions and policymakers can leverage these findings to design personalized investment solutions, promote market participation, and enhance financial decision-making frameworks. By understanding the underlying determinants of investment behavior, this study contributes to the growing discourse on improving investor engagement and fostering a more informed and efficient investment ecosystem.
Keywords: Financial Markets; Investment Choice Decision; Investment Objective; Liquidity; Risk & Return